The Role of Logistics Service Quality in Mediating the Influence of Air Cargo Packaging, Digital Information, and Air Cargo Tariff on Logistics Customer Retention at Silkargo Cikarang - Rahmad Ali Umar Dalimunthe; Melia Eka Lestiani; Agus Purnomo (Green Publisher Indonesia, 2026)
This research aims to analyze the influence of air cargo packaging, digital information, and air cargo tariffs on logistics customer retention through logistics service quality at SIL Kargo Cikarang. The background of this research is based on the decline in air cargo revenue from 2021 to 2025, the increasing rate of goods damage, digital misinformation, and relatively higher shipping rates compared to competitors. The research employed a quantitative approach using a survey method involving 125 customers of SIL Kargo Cikarang. The data analysis technique used was Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results of the study show that air cargo packaging, digital information, and air cargo tariffs have a positive and significant effect on logistics service quality. Logistics service quality also has a positive and significant effect on logistics customer retention and is able to mediate the influence of the three exogenous variables on logistics customer retention. These findings confirm that improving logistics service quality is a key strategy in retaining customers in the competitive air cargo industry.